2016
DOI: 10.1016/j.jad.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Sustained anterior cingulate cortex activation during reward processing predicts response to psychotherapy in major depressive disorder

Abstract: Background The purpose of the present investigation was to evaluate whether pre-treatment neural activation in response to rewards is a predictor of clinical response to Behavioral Activation Therapy for Depression (BATD), an empirically validated psychotherapy that decreases depressive symptoms by increasing engagement with rewarding stimuli and reducing avoidance behaviors. Methods Participants were 33 outpatients with major depressive disorder (MDD) and 20 matched controls. We examined group differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 74 publications
2
43
1
Order By: Relevance
“…Reward processing is complex and consists of sensory, attention and valuation components (Schultz, 2015). A number of brain structures are involved in reward processing, including the orbitofrontal cortex, medial prefrontal cortex, dorsolateral prefrontal cortex, motor cortex, parietal association cortex, visual cortex, striatum, and amygdala (Carl et al, 2016; Schultz, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Reward processing is complex and consists of sensory, attention and valuation components (Schultz, 2015). A number of brain structures are involved in reward processing, including the orbitofrontal cortex, medial prefrontal cortex, dorsolateral prefrontal cortex, motor cortex, parietal association cortex, visual cortex, striatum, and amygdala (Carl et al, 2016; Schultz, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…The insula, supplementary motor area, premotor cortex, occipital cortex, and cuneus were other regions of note where greater likelihood of activation was seen during reward anticipation (Table ). When this analysis was repeated using the eleven studies that only used a low magnitude reward (Behan et al, ; Carl et al, ; Choi et al, ; Damiano et al, ; Dillon et al, ; Figee et al, ; Jung et al, ; Kappel et al, ; Knutson, Bhanji, Cooney, Atlas, & Gotlib, ; Pfabigan et al, ; Romanczuk‐Seiferth, Koehler, Dreesen, Wüstenberg, & Heinz, ), we also found increased activation likelihood in the bilateral ventral and dorsal striatum, left supplementary motor and premotor areas and right insula (Table S, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 22 studies that examined reward receipt in some form, 13 used a contrast of successful reward outcome versus unsuccessful reward outcome (Bjork et al, ; Bjork, Smith, & Hommer, ; Boecker et al, ; Jung et al, ; Kirk et al, ; Knutson et al, ; Romanczuk‐Seiferth et al, ; Wu et al, ; Yan et al, ) and nine used successful reward outcome versus neutral trial outcome (Bustamante et al, ; Carl et al, ; Damiano et al, ; Dillon et al, ; Figee et al, ; Filbey et al, ; Hanssen et al, ; Mucci et al, ). To check if there was a difference between these two contrast types an additional ALE analysis was done.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioural activation (BA), for example, works by increasing engagement with reinforcers within the environment and overcoming avoidance [5]. Recent promising findings in adults show that greater pre-treatment anhedonia severity in a monetary reward processing task [77] and decreased neural functional connectivity, in a positive emotion upregulation task [78], are predictive of response to BA treatment. Further, BA is thought to be more cost effective and more acceptable to young people who are depressed than other psychotherapies [79], but it is still not effective for everyone.…”
Section: The Link Between Anhedonia and Reward Processing In Depressionmentioning
confidence: 99%